Pengaruh Aktivitas Galeri Investasi, Modal Minimal Dan Persepsi Risiko Terhadap Minat Investasi Saham Syariah: Studi Kasus Pada Mahasiswa FEBI UIN STS Jambi - Nur Indah Wulan Andriani; Eja Armaz Hardi; Aztyara Ismadharliani (Institut Nalanda, 2024)
Investment is a term that is no longer foreign and has become embedded in the world of economics and finance, in fact investment has become something that is of great interest to the general public and even students. Investment interest itself is a situation where a person has an interest in investing and tries to invest, with little capital, and to support this a person will continue to learn by attending seminars and discussions that discuss investment to reduce investment risk. This research aims to determine and analyze the influence of investment gallery activities, minimum capital and risk perception on interest in sharia stock investment. The method used in this research is a quantitative method with a data analysis method in the form of a coefficient of determination test. The sample in this research was 95 samples of FEBI UIN STS Jambi students class 2020-2022, by distributing a Likert scale questionnaire. The research results show that investment gallery activities influence interest in sharia stock investment as evidenced by a Sig value of 0,001 < 0,05. Minimum capital has no effect on interest in investing in sharia shares as evidenced by the Sig value of 0,264>0,05. Risk perception influences interest in investing in sharia shares as evidenced by the Sig value of 0,001<0,05. Investment gallery activities, minimum capital and risk perception together have a significant effect on interest in investing in sharia shares, with an Adjusted R Square value (coefficient of determination) of 0,644 or 64,4%, the remaining 35,6% is influenced by other variables outside this research. with a Standard Error Estimate of 3,523 or 35,23%.